Failure of Autologous Chondrocyte Implantation. Issue 1 (March 2017) - Andriolo, Luca; Merli, Giulia; Filardo, Giuseppe; Marcacci, Maurilio; Kon, Elizaveta
Abstract : Long-term results of autologous chondrocyte implantation and matrix-assisted autologous chondrocyte transplantation in the knee are satisfying, but not enough attention has been paid to the evaluation of failures. Thus, a systematic review of the literature was performed, underlining a failure rate in the 58 included articles of 14.9% among 4294 patients, most of them occurring in the first 5 years after surgery, and with no difference between autologous chondrocyte implantation and matrix-assisted autologous chondrocyte transplantation. Failures are very heterogenously defined in the current literature. A widely accepted definition is needed, and a comprehensive definition taking into consideration the patient's perception of the outcome, not just the surgeon's or researcher's point of view, would be advisable. Finally, there is no agreement on the most appropriate treatment of failures, and further studies are needed to give better indications to properly manage patients failed after cartilage procedures. Level of Evidence : Level IV.